Peran Guru Dalam Meningkatkan Motivasi Belajar Pendidikan Agama Islam Di Era Digital - Taufik Taufik; Amaluddin Amaluddin (FKIP UNSULTRA, 2025)
The development of digital technology has had a major impact on various aspects of life, including in the world of education. Islamic Religious Education (PAI) as part of the national curriculum also faces new challenges and opportunities in the learning process. One of the main challenges is maintaining and increasing students' learning motivation which is increasingly distracted by various digital platforms. This literature study aims to examine in depth the role of teachers in increasing PAI learning motivation in the digital era. This study uses a qualitative approach with a literature study method from various sources such as scientific journals, reference books, and the latest academic articles. The results of the study show that teachers have a strategic role not only as material deliverers, but also as facilitators, motivators, innovators, and spiritual guides who are able to adapt technology in the learning process. Teachers who are able to utilize digital media effectively, develop technology-based learning strategies, and build emotional closeness with students will be more successful in increasing their learning motivation. Therefore, it is necessary to strengthen the digital and pedagogical competencies of teachers in order to be able to answer the challenges of PAI learning in the digital era. This study provides recommendations for the development of teacher training and the integration of technology into the PAI curriculum.